Effect of Multicomponent Exercise Program on Temporomandibular Joint Dysfunction in Oral Cancer Survivors - Sandeep Shinde; Ishana Kadam; Shivanee Dalvi; Pooja Jain; Sanjaykumar Patil; Anand Gudur (Journal of Head & Neck Physicians and Surgeons)
Introduction: Cancer is the second most cause of mortality among which oral cancer is the most prevalent form. In temporomandibular joint dysfunction (TMJD), patients present with pain, restricted mouth opening, poor posture, facial asymmetry, diminished strength, altered breathing patterns, decreased deglutition, and poor eating habits The objective of this research was to determine and compare the effect of a multicomponent exercise program with conventional physiotherapy program for TMJD in oral cancer survivors. Materials and Methods: This study included 100 participants with TMJD based on inclusion and exclusion criteria. Then, the subjects were randomly allocated into Group A and Group B by a simple random sampling method. Group A was given a conventional physiotherapy exercise program and for Group B multicomponent exercise program was given. Outcome measures used were a Visual Analog Scale, assessment of range of motion (ROM) and manual muscle testing (MMT) and the American Academy of Orofacial Pain questionnaire. Pre- and post-assessment of the above measures was taken to confirm the results. Results: The results showed a statistically significant effect of the multicomponent exercise program as compared to a conventional exercise program for TMJD in oral cancer survivors. There was a significant reduction in pain (<0.0001) in individuals in Group B than in Group A. Restriction in the ROM and improvement in MMT were also significantly (P < 0.0001) resolved and the facial symmetry, breathing patterns as well as swallowing difficulty were also improved. Conclusion: On the basis of the results, it can be concluded that the Group B who followed the multicomponent exercise program showed better improvement in pain intensity, ROM, facial symmetry, muscle strength, breathing pattern and in swallowing as compared to Group A. Similarly utilizing a multifaceted patient-centered approach has been proven to be effective and lead to successful recovery of the temporomandibular joint function in oral cancer survivors.